Hydrothermal growth of ZnO nanowire arrays: fine tuning by precursor supersaturation. Issue 3 (5th January 2017) - Yan, Danhua; Cen, Jiajie; Zhang, Wenrui; Orlov, Alexander; Liu, Mingzhao
Abstract : Novel syringe-pump assisted hydrothermal growth fine tunes ZnO nanowire arrays into the desired morphology by precise control of supersaturation. Abstract : Here we develop a technique that fine tunes the hydrothermal growth of ZnO nanowires to address the difficulties in controlling their growth in a conventional one-pot hydrothermal method. In our technique, precursors are separately and slowly supplied with the assistance of a syringe pump, through the entire course of the growth. Compared to the one-pot method, the significantly lowered supersaturation of precursors helps eliminating competitive homogeneous nucleation and improves the reproducibility. The supersaturation degree can be readily tuned by the precursor quantity and injection rate, thus forming ZnO nanowire arrays of various geometries and packing densities in a highly controllable fashion. The precise control of ZnO nanowire growth enables systematic studies on the correlation between the material's properties and its morphology. In this work, ZnO nanowire arrays of various morphologies are studied as photoelectrochemical (PEC) water splitting photoanodes, in which we establish clear correlations between the water splitting performance and the nanowires' size, shape, and packing density.